2003
DOI: 10.1677/joe.0.1760111
|View full text |Cite
|
Sign up to set email alerts
|

Neurohypophysial hormone regulation of Cl- secretion: physiological evidence for V1-type receptors in sea bass gill respiratory cells in culture

Abstract: Neurohypophysial hormone receptors were studied in primary cultures of sea bass (Dicentrarchus labrax) gill respiratory-like cells grown on permeable supports. This preparation was previously shown to provide a functional model for investigating the hormonal regulation of Cl secretion.Under control conditions, the cultured monolayered epithelium had a short-circuit current (I SC ) of 3·5 1·1 µA cm 2 . This current had previously been identified as an active Cl secretion. The addition of increasing concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 26 publications
1
22
1
Order By: Relevance
“…The pattern of changes in plasma AVT and IT levels (see above), as well as expression of the AVT and IT receptors within the gill (Fig. 7), suggests that stimulation of the vasotocinergic and isotocinergic systems could be important for increasing sodium and chloride secretion during the initial stress period, which has previously been described in Carassius auratus (Maetz et al, 1964) and following hormonal administration to gill respiratory cell culture in Dicentrarchus labrax (Guibbolini and Avella, 2003).…”
Section: Gillmentioning
confidence: 53%
“…The pattern of changes in plasma AVT and IT levels (see above), as well as expression of the AVT and IT receptors within the gill (Fig. 7), suggests that stimulation of the vasotocinergic and isotocinergic systems could be important for increasing sodium and chloride secretion during the initial stress period, which has previously been described in Carassius auratus (Maetz et al, 1964) and following hormonal administration to gill respiratory cell culture in Dicentrarchus labrax (Guibbolini and Avella, 2003).…”
Section: Gillmentioning
confidence: 53%
“…The V1a receptor is the dominant one expressed in the brain (Strand 1999) and, while the V2 receptor mainly has a peripheral distribution, the V1b receptor is also distributed in the brain (Strand 1999) making it a candidate also to mediate behavioural modulation by AVT. While only V1-type receptors have so far been identified in teleosts (Mahlmann et al 1994;Warne 2001;Guibbolini & Avella 2003), the presence of multiple AVT receptor subtypes in other taxa at least suggests their presence and possible co-modulation of behaviour among teleosts.…”
Section: Discussionmentioning
confidence: 99%
“…However, Manning compound, an AVP antagonist specific to the V1a receptor (see Barberis et al 1999) that is commonly used as an AVT V1 receptor antagonist in teleosts (e.g. Mahlmann et al 1994;Goodson & Bass 2000a;Guibbolini & Avella 2003), does not show the reciprocal effect. Manning compound decreases T-TP aggression towards IP males, but has no influence on T-TP aggression towards T-TP males (Semsar et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…VT administration caused an increase in urine volume, osmolarity and sodium levels in hypophysectomized catfish (Parwez and Goswami 1985). Studies in other fishes have also shown that VT secretion is sensitive to changes in environmental salinity, which regulates water and ionic exchanges through the cognate receptors (Mahlmann et al 1994;Kulczykowska 2001;Warne 2001;Warne et al 2002;Guibbolini and Avella 2003;Balment et al 2006). In the catfish, the three VT receptor subtype genes are expressed in the gill and kidney in both sexes, implying a VT regulation of their functions.…”
Section: Tissue Expression Patternmentioning
confidence: 98%
“…In the trout Oncorhynchus mykiss, Conklin et al (1999) characterized pharmacologically the V1A-type receptor that mediated the VT-induced vascular smooth muscle contraction. In cultured gill epithelium of European sea bass (Dicentrarchus labrax), VT and the V1-type receptor agonist [Phe2, Orn8]-oxytocin were found to stimulate Cl -secretion while the V2-type receptor agonist failed to produce any effect (Guibbolini and Avella 2003). A V2-type receptor, or at least one that acted by altering the intracellular cAMP level, was reported in isolated renal tubules from the rainbow trout by Perrott et al (1993).…”
Section: Introductionmentioning
confidence: 99%